2015
DOI: 10.1155/2015/458123
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Alterations in the Expression of Genes and Synaptic Plasticity Associated with Nitric Oxide Signaling in the Mouse Dorsal Striatum

Abstract: Age-related alterations in the expression of genes and corticostriatal synaptic plasticity were studied in the dorsal striatum of mice of four age groups from young (2-3 months old) to old (18–24 months of age) animals. A significant decrease in transcripts encoding neuronal nitric oxide (NO) synthase and receptors involved in its activation (NR1 subunit of the glutamate NMDA receptor and D1 dopamine receptor) was found in the striatum of old mice using gene array and real-time RT-PCR analysis. The old striatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Aging-related increases in astrocyte activation, determined by GFAP mRNA and protein expression, have been found in several areas of the brain including CORT [83,84], CERE [83], striatum [85], and hippocampus [86]. We showed in this study that long-term Tat expression led to increased GFAP expression in both CORT and CPU, decreased GFAP expression in CERE and no changes in HIP (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Aging-related increases in astrocyte activation, determined by GFAP mRNA and protein expression, have been found in several areas of the brain including CORT [83,84], CERE [83], striatum [85], and hippocampus [86]. We showed in this study that long-term Tat expression led to increased GFAP expression in both CORT and CPU, decreased GFAP expression in CERE and no changes in HIP (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…We performed a between-genotypes comparison of mRNA levels encoding for the selected neurotransmitter receptors, enzymes and structural proteins involved in synaptic plasticity. Using first PCR array “Mouse Nitric Oxide Signaling Pathway” (PAMM-062Z, SA Bioscience) as described in Chepkova et al 25. we detected a 2-fold upregulation of beta-actin expression in striatal tissue of LGS-ko mice with no change in any other gene transcripts when reactions were normalized on beta-2-microglobulin (B2m), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and glucuronidase beta (Gusb).…”
Section: Resultsmentioning
confidence: 98%
“…We analyzed the expression of genes encoding receptors for neurotransmitters, known to be involved in hippocampal and corticostriatal plasticity (glutamate, dopamine, acetylcholine, endocannabinoids) and other plasticity-related proteins. Detailed description of the applied protocol was presented previously25. The relative mRNA level encoding each gene was estimated by the 2 −ΔΔCt method described previously2578, where ΔCt = Ct target gene – Ct Rpl13a (ribosomal protein L13a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown age-related modifications in the NMDA receptor-NO-cGMP cascade in the CNS (Peterson and Cotman, 1989 ; Tamaru et al, 1991 ; Wenk et al, 1991 ; Vallebuona and Raiteri, 1995 ; Wardas et al, 1997 ; Ossowska et al, 2001 ; Chepkova et al, 2015 ). In addition, the aging process is associated with a progressive decline in NKA activity, both centrally and peripherally (Scavone et al, 2000 ; Kawamoto et al, 2008 ; Vasconcelos et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%